1996
DOI: 10.1074/jbc.271.34.20895
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Endoplasmic Reticulum Retention of Unassembled α- and β-Subunits of Na,K-ATPase Correlate with Interaction of BiP

Abstract: Assembly of ␣-and ␤-subunits in the endoplasmic reticulum is a prerequisite for the structural and functional maturation of oligomeric P-type ATPases. In Xenopus oocytes, overexpressed, unassembled ␣-and ␤-subunits of Xenopus Na,K-ATPase are retained in the endoplasmic reticulum (ER) and are degraded with different kinetics, while unassembled ␤-subunits of gastric H,K-ATPase leave the ER. In this study, we have investigated the role of the immunoglobulin-binding protein, BiP, in the folding, assembly, and ER r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 54 publications
6
46
0
Order By: Relevance
“…P␣F might have become bound to and trapped in the ER by exaggerated amounts of BiP (Figure 9), but the concentrations and/or activities of cochaperones required for release might not have risen in parallel. Consistent with our work, increasing the level of BiP slows the ERAD of mutant ribophorin in mammalian cells (deVirgilio et al, 1999) and the concept that ERAD can proceed only after BiP release is well established (Knittler et al, 1995;Beggah et al, 1996;Skowronek et al, 1998;Chillaron and Haas, 2000). It is possible that under conditions of ER stress, when the concentration of BiP rises via the UPR, ERAD efficiency may decline, but the solubility of putative ERAD substrates is maintained.…”
Section: Erad-defective Mutations In Bip/kar2psupporting
confidence: 71%
See 1 more Smart Citation
“…P␣F might have become bound to and trapped in the ER by exaggerated amounts of BiP (Figure 9), but the concentrations and/or activities of cochaperones required for release might not have risen in parallel. Consistent with our work, increasing the level of BiP slows the ERAD of mutant ribophorin in mammalian cells (deVirgilio et al, 1999) and the concept that ERAD can proceed only after BiP release is well established (Knittler et al, 1995;Beggah et al, 1996;Skowronek et al, 1998;Chillaron and Haas, 2000). It is possible that under conditions of ER stress, when the concentration of BiP rises via the UPR, ERAD efficiency may decline, but the solubility of putative ERAD substrates is maintained.…”
Section: Erad-defective Mutations In Bip/kar2psupporting
confidence: 71%
“…In accordance with these hypotheses, several lines of evidence support a role for the lumenal Hsp70, BiP, in ERAD in both mammals and yeast. First, the proteolysis of ERAD substrates coincides with the rate at which they are released from BiP in the mammalian ER (Knittler et al, 1995;Beggah et al, 1996;Skowronek et al, 1998;Chillaron and Haas, 2000), and BiP associates preferentially with exposed regions of an unfolded ERAD substrate (Schmitz et al, 1995). Second, the degradation of an ERAD substrate is slowed when yeast contain a mutant allele in the gene encoding BiP, KAR2 (kar2-113;Plemper et al, 1997), and two ERAD substrates in yeast, CPY* and p␣F, aggregate in microsomes prepared from another kar2 mutant shifted to the nonpermissive temperature (kar2-203;Nishikawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Na, K-ATPase consists of α and β subunits. The glycosylated β subunit has been proposed to facilitate the assembly and transport of the α subunit from the endoplasmic reticulum to the plasma membrane (20,21), and the β subunit is the key factor in polarizing distribution of Na, K-ATPase (22). The results of the present study showed that the HCMV UL136 protein has the ability to interact with ATP1B1.…”
Section: Discussionsupporting
confidence: 54%
“…Newly synthesized proteins are screened by ER resident proteins, immunoglobulin binding proteins (BiP). Misfolded poly-peptides and unassembled subunits of oligomeric proteins are captured by BiP, retained in the ER, and rapidly degraded in the lumen of the ER (Bonifacino et al, 1989;Klausner and Sitia, 1990;Sitia et al, 1990;Wileman et al, 1990;Wikstorm and Lodish, 1992;Beggah et al, 1996). This rapid and selective degradation of proteins have been described as preGolgi or ER degradation (Lippincoctt-Scchwartz et al , 1988).…”
Section: Introductionmentioning
confidence: 99%